Method for preparing carbon-ceramic composite material brake disc through 3D printing

By pretreatment and mixing of modified chopped carbon fiber and other raw materials, combined with 3D printing technology, the problems of poor raw material extrusion performance and uneven discharge of carbon ceramic brake discs during 3D printing are solved, and the brake discs are improved The mechanical properties and production efficiency simplify the production process.

CN119191864AInactive Publication Date: 2024-12-27SHANDONG JINGCHENG NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411325612.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the 3D printing and preparation process, existing carbon ceramic brake discs have problems such as poor raw material extrusion performance, uneven printing and discharge, and easy to block the nozzle of the 3D printer, resulting in unstable brake disc performance and low production efficiency.

Method used

Pretreatment and mixing of modified chopped carbon fiber, alumina, octadecanoic acid, sodium hyposulfite, N-(hydroxymethyl)acrylamide, lauryl acrylate and other raw materials, and prepare carbon ceramic composite brake discs through 3D printing technology , combine the glue discharge and sintering process to improve the uniformity and bonding performance of raw materials, avoid blockage, and improve production efficiency.

Benefits of technology

Effectively reduce raw material waste, improve the mechanical and wear resistance of carbon ceramic brake discs, enhance brake performance, simplify the production process, reduce costs, and improve production efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a method for preparing a carbon-ceramic composite material brake disc through 3D printing, and belongs to the field of brake discs. The invention discloses a carbon-ceramic composite material brake disc. The light-cured carbon fiber composite material is prepared from the following raw materials: 45-70 parts of modified short carbon fiber, 1-5 parts of boron carbide, 30-40 parts of light-cured resin, 2-8 parts of 75 # microcrystalline wax, 3-8 parts of liquid paraffin, 2-5 parts of aluminum oxide, 2-5 parts of aluminum nitride, 2-6 parts of carbon black, 2-6 parts of octadecanoic acid, 1-5 parts of a modified dispersant, 1-3 parts of an emulsifier, 1-3 parts of ethanolamine, 1-4 parts of sucrose fatty acid ester, 2-6 parts of nitrile rubber powder and 8-20 parts of an organic solvent. According to the method for preparing the carbon-ceramic composite material brake disc through 3D printing, the problems that in the 3D printing process, the extrusion performance of raw materials is poor, printing discharging is uneven, and a nozzle is prone to being blocked can be solved, the curing forming effect and the production efficiency are improved, and the mechanical performance and wear resistance of the brake disc are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of brake materials, and in particular to a method for preparing a carbon-ceramic composite brake disc by 3D printing. Background Art

[0002] In recent years, the automobile industry has developed rapidly, and the automobile market has expanded rapidly along with the substantial increase in the number of cars in use. With the rapid growth of the automobile market and the rapid increase in the number of cars in recent years, the AM market for automobile brake parts contains great business opportunities. However, the performance level of existing brake parts is relatively low. Since the end of the 19th century, the mainstream brake disc material of automobiles, gray cast iron, has a serious thermal decay phenomenon during actual use, and has gradually failed to meet the current market's requirements for automobile performance.

[0003] In recent years, carbon ceramic brake discs developed with existing technologies have lower thermal decay than gray cast iron brake discs, and are lighter, have shorter braking distances, less braking noise, longer service life, and are more corrosion-resistant. It can be said that carbon ceramic brake discs completely crush gray cast iron brake discs in terms of braking performance; at the same time, existing experiments have proved that carbon ceramic brake discs have significant results in saving fuel and electricity consumption per 100 kilometers, and are the upgrade direction of automotive brake materials. However, the production cost of existing carbon ceramic brake discs is extremely high, and they are currently only partially used in high-end cars and racing cars.

[0004] As people's requirements for automobile driving quality increase, the demand for carbon-ceramic brake discs is also increasing. The raw material consumption of carbon-ceramic brake discs and associated brake components in the experimental process of improving their performance and appearance is immeasurable; and it is difficult to prepare carbon-ceramic parts with complex shapes using conventional processes, the waste of raw materials is uncontrollable, and the production scrap rate is high; further, the existing carbon-ceramic brake discs have poor heating uniformity during the preparation process, the performance of the prepared brake discs is unstable, the relevant performance indicators of the brake discs (such as strength, hardness, toughness, wear resistance, etc.) fluctuate greatly, and the quality stability is poor.

[0005] In response to the above-mentioned technical defects, the inventors specifically adopted 3D printing technology to prepare brake discs and their ancillary parts. However, after a large number of experiments and studies, the inventors found that in the process of using existing carbon ceramic materials for 3D printing to prepare brake discs and their ancillary parts, there are problems such as poor raw material extrusion performance, uneven printing output, and easy clogging of the 3D printer nozzle during the printing process. This not only seriously affects the curing molding effect and production efficiency of 3D printing, but also leads to the problem of unstable mechanical properties, poor wear resistance and thermal shock resistance of the final carbon ceramic brake disc. Summary of the invention

[0006] In order to solve the technical problems existing in the prior art, the present invention provides a method for preparing a carbon-ceramic composite brake disc by 3D printing, which can effectively reduce raw material waste and improve the performance stability of the brake disc, while further overcoming the problems of poor raw material extrusion performance, uneven printing, and easy clogging of the 3D printer nozzle during the printing process when using existing carbon-ceramic materials to prepare brake discs and their ancillary parts by 3D printing, effectively improving the curing molding effect and production efficiency, and improving the mechanical properties and wear resistance of the finally prepared carbon-ceramic brake disc.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a carbon-ceramic composite brake disc by 3D printing, wherein the raw materials of the carbon-ceramic composite brake disc include, by weight: 45-70 parts of modified chopped carbon fiber, 1-5 parts of boron carbide, 30-40 parts of light-cured resin, 2-8 parts of 75# microcrystalline wax, 3-8 parts of liquid paraffin, 2-5 parts of aluminum oxide, 2-5 parts of aluminum nitride, 2-6 parts of carbon black, 2-6 parts of octadecanoic acid, 1-5 parts of modified dispersant, 1-3 parts of emulsifier, 1-3 parts of ethanolamine, 1-4 parts of sucrose fatty acid ester, 2-6 parts of nitrile rubber powder, and 8-20 parts of organic solvent; The raw materials are premixed, pounded and granulated, and then 3D printed to obtain a brake disc green body, and then debinding and sintering are performed to obtain a carbon-ceramic composite brake disc.

[0008] Preferably, the particle size of the carbon black is 1nm-100nm, the particle size of the aluminum oxide is 500nm-800nm, and the particle size of the aluminum nitride is 2-20μm; The emulsifier is at least one of the following: fatty alcohol polyoxyethylene ether, fatty acid methyl ester polyoxyethylene ether, and sodium carboxymethyl cellulose; The organic solvent is at least one of the following: ethanol, tetrahydrofuran, styrene, perchloroethylene, and ethylene glycol ether.

[0009] Furthermore, the preparation method of the modified chopped carbon fiber is as follows: heat-treating the chopped carbon fiber in an argon atmosphere at 1200-1800°C for 2-2.5h to remove metal ions and impurities on the surface of the chopped carbon fiber; then putting it into acetone, ultrasonically cleaning it until there is no glue on the surface, placing it in an oven after cleaning, and drying it until the acetone is completely volatilized; then immersing the treated chopped carbon fiber into the modified treatment liquid, soaking it at 28-36°C for 10-25h, washing it with distilled water and drying it to obtain the modified chopped carbon fiber.

[0010] Preferably, the modified treatment liquid is an ethanol solution of tetraisopropyl di(dioctylphosphite) titanate; in the modified treatment liquid, the concentration of tetraisopropyl di(dioctylphosphite) titanate is 3-3.3wt%, and the concentration of the ethanol solution is 85-90%; The diameter of the chopped carbon fiber is 6-20 μm and the length is 2-20 mm.

[0011] Furthermore, the preparation method of the modified dispersant is as follows: alumina, octadecanoic acid, sodium hyposulfite, N-(hydroxymethyl)acrylamide, diethylenetriamine, lauryl acrylate and deionized water are mixed evenly and then allowed to stand for 1-3 hours to obtain a mixture; the mixture is placed in a vacuum homogenizer, and vacuum homogenized for 0.5-1 hour at a vacuum degree of 0.01-0.059 MPa and a rotation speed of 3000-4300 rpm. After the vacuum homogenization is completed, the mixture is placed in a temperature environment of 95-100°C and dried for 50-120 minutes to obtain a modified dispersant in a slurry state.

[0012] Preferably, the mass ratio of aluminum oxide, octadecanoic acid, sodium hyposulfite, N-(hydroxymethyl)acrylamide, diethylenetriamine, lauryl acrylate, and deionized water is 12-35:15-30:3-5:3-8:2-5:1-2:25-55.

[0013] Furthermore, the method for preparing the premix is ​​as follows: by weight, short chopped carbon fiber, boron carbide, adhesive, 75# microcrystalline wax, liquid paraffin, alumina, aluminum nitride, carbon black, octadecanoic acid, modified dispersant, emulsifier, ethanolamine, sucrose fatty acid ester, nitrile rubber powder, and organic solvent are put into a mixer, the stirring speed is controlled to be 900-1300 rpm, and the premix is ​​obtained after stirring and mixing for 15-45 minutes.

[0014] Furthermore, the method for internal mixing is as follows: introducing the premix obtained in the premixing step into the internal mixing chamber of the internal mixer, setting the temperature of the internal mixing chamber to 210-250°C, the internal mixing speed to 10-15r / min, starting the internal mixer to heat and the main shaft to rotate forward, and performing internal mixing; observing the state of the material in the internal mixing chamber at any time during the internal mixing process, and ending the internal mixing after 50-100 minutes of internal mixing if the material is viscous and moderately soft and hard; starting cooling, and waiting for the material in the internal mixing chamber to cool to 40-60°C, discharging the material to obtain the internal mixed material.

[0015] Furthermore, the granulation method is as follows: placing the mixed material obtained in the mixing step in the feeding zone of the granulator, setting the feeding temperature to 35-55°C, and the feeding speed to 5-8r / min; turning on the heating, pre-heating the screw zone and the discharging zone of the granulator, setting the screw zone temperature to 180-240°C, the screw zone speed to 5-8r / min, the discharging zone temperature to 170-215°C, and the discharging zone speed to 1.5-3.5r / min; after the temperatures of the screw zone and the discharging zone reach the set values, starting the forward rotation of the screw in the feeding zone, the forward rotation of the screw in the discharging zone, and the forward rotation of the screw in the screw zone in turn to carry out granulation, and observing the discharging situation during the granulation process, and fine-tuning the speed according to the discharging situation to obtain uniform particles and non-adhesive particles.

[0016] Furthermore, the 3D printing method is to put the granules obtained in the granulation step into the hopper of the 3D printer, start automatic loading, use a nozzle with a diameter of 0.4-0.8mm, set the printing layer height to 0.15-0.35mm, the starting layer height to 0.15-0.35mm, the printing temperature to 210-250℃, the platform temperature to 100-140℃, and the printing speed to 35-55mm / s; and adjust the distance between the platform and the nozzle to 0.13-0.15mm; after importing the three-dimensional image of the brake disc into the slicing program, import the slicing program into the 3D printer for 3D printing, cool after printing, and obtain the brake disc green body.

[0017] Furthermore, the debinding method is to place the brake disc green body in a vacuum environment of 0.04-0.06MPa, heat it to 700-1200°C under the protection of a nitrogen atmosphere, keep it warm for 80-360 minutes to debind, and cool it to room temperature after debinding to obtain a porous green body.

[0018] Furthermore, during the sintering, the porous green body obtained in the debinding step is placed in a vacuum environment of 10-30Pa, silicon powder is added to the middle crucible where the porous green body is located, and then nitrogen is introduced as a protective gas, and the temperature is increased to 1530-2100°C at a heating rate of 7-9°C / min, and the green body is sintered at this temperature for 65-130min; and during the sintering process, a suction device is used to suck the molten silicon powder into the porous green body; after the sintering is completed, the temperature is naturally lowered to room temperature to obtain a brake disc preform.

[0019] Preferably, the added weight of silicon powder is 3-10% of the weight of the porous green body.

[0020] Furthermore, the de-weighting assembly method is to clean the powder and dust deposits in the grooves and pores of the sintered brake disc preform, assemble it according to the requirements of the drawing, and obtain the carbon-ceramic composite material brake disc to be inspected.

[0021] Furthermore, the non-destructive testing method is to use an ultrasonic flaw detector to conduct a finished product qualification test on the carbon-ceramic composite brake disc to be inspected, and judge the test results by the waveforms of longitudinal waves, transverse waves, surface waves, and plate waves. If the test is qualified, a carbon-ceramic composite brake disc is obtained.

[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The method for preparing a carbon-ceramic composite brake disc by 3D printing of the present invention is aimed at 3D printing characteristics. By using a specific amount of raw materials for combination, and using a coordinated titanate coupling agent solution to modify the heat-treated chopped carbon fiber, a modified chopped carbon fiber is obtained. While improving the effect of impurities in the chopped carbon fiber on the performance of the brake disc, the bonding performance between the raw materials is improved. At the same time, a modified dispersant is pre-prepared using aluminum oxide, octadecanoic acid, sodium hyposulfite, N-(hydroxymethyl) acrylamide, diethylenetriamine, and lauryl acrylate. The modified dispersant is combined with the raw materials to further improve the compatibility of the raw materials with 3D printing. The raw materials are mixed, kneaded and granulated to improve the uniformity of the raw materials and the extrusion performance of the raw materials during 3D printing. The printed material is uniform, which improves the uniformity of the prepared brake disc green body, further avoids the clogging of the printer nozzle, and improves production efficiency; then 3D printing is performed to prepare the brake disc green body, and the brake disc green body is subjected to processes such as debinding and sintering to obtain a carbon-ceramic composite brake disc, which can effectively reduce raw material waste and improve the performance stability of the brake disc. At the same time, it can further overcome the problems of poor raw material extrusion performance, uneven printing, and easy clogging of the 3D printer nozzle during the printing process when using existing carbon-ceramic materials to prepare brake discs and their ancillary parts by 3D printing, effectively improve the curing molding effect and production efficiency, improve the mechanical properties and wear resistance of the finally prepared carbon-ceramic brake disc, and thus improve the braking performance of the carbon-ceramic composite brake disc.

[0023] (2) The method of preparing carbon-ceramic composite brake discs by 3D printing of the present invention uses carbon-ceramic composite materials to prepare brake discs. Based on the advantages of low density, high strength, high thermal conductivity, good friction performance, and light thermal decay of carbon-carbon composite materials, it can effectively overcome the problem of large attenuation of wet friction coefficient of traditional brake discs and further optimize the comprehensive performance of brake discs.

[0024] (3) The method of preparing carbon-ceramic composite brake discs by 3D printing of the present invention adopts 3D printing to prepare brake discs, without the need for additional mold assistance and subsequent mechanical finishing and shaping, thereby reducing the number of mold openings, simplifying the production process, and reducing production and assembly costs, consumable costs, and labor costs; and through one-time molding by 3D printing, it effectively reduces raw material waste, improves raw material utilization, and shortens the production and R&D cycle of brake discs.

[0025] (4) The method of preparing carbon-ceramic composite brake discs by 3D printing of the present invention adopts 3D printing to prepare brake discs, which effectively improves the design and production efficiency of products; under the existing production technology conditions, the production and manufacturing of non-standard equipment products can be realized more efficiently and economically, greatly improving production efficiency.

[0026] (5) The method for preparing a carbon-ceramic composite brake disc by 3D printing of the present invention has a volume density of more than 2.8 g / cm³, a bending strength of up to 420 MPa, a friction coefficient of 0.36-0.41, and a wear rate reduced to 0.3×10 -7 cm³ / (N·m), can withstand a maximum temperature of 1920°C, and has good thermal shock resistance. DETAILED DESCRIPTION

[0027] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0028] Example 1 The present embodiment provides a method for preparing a carbon-ceramic composite brake disc by 3D printing. The raw materials of the carbon-ceramic composite brake disc include, by weight: 45 parts of modified chopped carbon fibers, 1 part of boron carbide, 30 parts of photocurable resin, 2 parts of 75# microcrystalline wax, 3 parts of liquid paraffin, 3 parts of alumina, 2 parts of aluminum nitride, 4 parts of carbon black, 4 parts of octadecanoic acid, 1 part of modified dispersant, 2 parts of carboxymethyl cellulose (emulsifier), 3 parts of ethanolamine, 2 parts of sucrose fatty acid ester, 6 parts of nitrile rubber powder, and 17 parts of tetrahydrofuran (organic solvent).

[0029] The particle size of the carbon black is 50 nm, the particle size of the aluminum oxide is 600 nm, and the particle size of the aluminum nitride is 10 μm.

[0030] The preparation method of the modified chopped carbon fiber comprises the following steps: heat-treating the chopped carbon fiber in an argon atmosphere at 1200° C. for 2 hours to remove metal ions and impurities on the surface of the chopped carbon fiber; then putting the chopped carbon fiber into acetone, ultrasonically cleaning it until there is no glue on the surface, placing it in an oven after cleaning, and drying it until the acetone is completely volatilized; then immersing the treated chopped carbon fiber into a modified treatment liquid, soaking it at 28° C. for 10 hours, washing it with distilled water, and then drying it to obtain the modified chopped carbon fiber.

[0031] The modified treatment liquid is an ethanol solution of tetraisopropyl di(dioctylphosphite) titanate; in the modified treatment liquid, the concentration of tetraisopropyl di(dioctylphosphite) titanate is 3wt%, and the concentration of the ethanol solution is 85%.

[0032] The diameter of the chopped carbon fibers was 10 μm and the length was 12 mm.

[0033] The preparation method of the modified dispersant comprises the following steps: mixing aluminum oxide, octadecanoic acid, sodium hyposulfite, N-(hydroxymethyl) acrylamide, diethylenetriamine, lauryl acrylate and deionized water in a mass ratio of 20:20:3:3:2:1:51, and then standing for 1.5 hours to obtain a mixture; placing the mixture in a vacuum homogenizer, performing vacuum homogenization for 0.5 hours at a vacuum degree of 0.015 MPa and a rotation speed of 3200 rpm, and placing the mixture in a 95° C. temperature environment after the vacuum homogenization, and drying for 50 minutes to obtain a slurry-state modified dispersant; The method for preparing a carbon-ceramic composite brake disc by 3D printing is specifically as follows: 1. Premix According to weight, short carbon fiber, boron carbide, adhesive, 75# microcrystalline wax, liquid paraffin, alumina, aluminum nitride, carbon black, octadecanoic acid, modified dispersant, emulsifier, ethanolamine, sucrose fatty acid ester, nitrile rubber powder, and organic solvent are put into a mixer, the stirring speed is controlled to 900 rpm, and after stirring and mixing for 20 minutes, a premix is ​​obtained.

[0034] 2. Secret refining The premix prepared in the premixing step is introduced into the mixing chamber of the internal mixer, the temperature of the internal mixer is set to 220°C, the mixing speed is set to 10r / min, the internal mixer is turned on for heating and the main shaft is turned on for forward rotation, and internal mixing is performed; during the internal mixing process, the state of the material in the internal mixing chamber is observed at any time, and after 50 minutes of internal mixing, the material is viscous and has moderate hardness and softness, and the internal mixing is terminated; the cooling is started, and the material in the internal mixing chamber is cooled to 45°C, and then the material is discharged to obtain the internally mixed material.

[0035] 3. Granulation The mixed material obtained in the mixing step is placed in the feeding area of ​​the granulator, and the feeding temperature is set to 35°C and the feeding speed is set to 5r / min; the heating is turned on to pre-heat the screw zone and the discharging zone of the granulator, and the temperature of the screw zone is set to 180°C and the speed of the screw zone is set to 5r / min, and the temperature of the discharging zone is set to 170°C and the speed of the discharging zone is set to 2r / min; after the temperatures of the screw zone and the discharging zone reach the set values, the screw of the feeding zone, the screw of the discharging zone and the screw zone are turned on in sequence to carry out granulation, and the discharging situation is observed during the granulation process, and the speed is fine-tuned according to the discharging situation to obtain granules with uniform particles and no adhesion.

[0036] 4. 3D printing Put the granules obtained in the granulation step into the hopper of the 3D printer, turn on automatic loading, use a nozzle with a diameter of 0.4mm, set the printing layer height to 0.15mm, the starting layer height to 0.2mm, the printing temperature to 210℃, the platform temperature to 120℃, and the printing speed to 35mm / s; and adjust the distance between the platform and the nozzle to 0.13mm; after importing the three-dimensional image of the brake disc into the slicing program, import the slicing program into the 3D printer for 3D printing, cool it after printing, and obtain the brake disc green body.

[0037] 5. Debinding The brake disc green body was placed in a vacuum environment of 0.04 MPa, and under the protection of a nitrogen atmosphere, the temperature was raised to 700°C, and the temperature was kept for 80 minutes for debinding. After the debinding was completed, the green body was cooled to room temperature to obtain a porous green body.

[0038] 6. Sintering The porous green body obtained in the debinding step is placed in a vacuum environment of 10Pa, silicon powder is added to the middle crucible where the porous green body is located, and then nitrogen is introduced as a protective gas, and the temperature is increased to 1530°C at a heating rate of 7°C / min, and the green body is sintered for 65 minutes; and during the sintering process, a suction device is used to suck the molten silicon powder into the porous green body; after the sintering is completed, the temperature is naturally cooled to room temperature to obtain a brake disc preform.

[0039] The added weight of silicon powder is 3% of the weight of the porous green body.

[0040] 7. Remove heavy assembly The powder and dust deposits in the grooves and pores of the sintered brake disc preform are cleaned up, and the preform is assembled according to the requirements of the drawing to obtain a carbon-ceramic composite brake disc to be inspected.

[0041] 8. Nondestructive testing An ultrasonic flaw detector is used to conduct finished product qualification test on the carbon-ceramic composite brake disc to be inspected. The test results are judged by the waveforms of longitudinal wave, transverse wave, surface wave and plate wave. If the test is qualified, the carbon-ceramic composite brake disc is produced.

[0042] After testing, the volume density is 2.8g / cm³, the bending strength is 412MPa, the friction coefficient is 0.38, and the wear rate is 0.3×10 -7 cm³ / (N·m), and can withstand high temperatures of 1825°C.

[0043] Furthermore, the carbon-ceramic composite brake disc of this embodiment is placed in a calcining furnace, and in an air atmosphere environment, the temperature is increased to 1200°C at a heating rate of 20°C / min, and after being kept warm for 10 hours, it is cooled to room temperature at a cooling rate of 10°C / min; after repeating this process 20 times, the bending strength of the carbon-ceramic composite brake disc can still reach 397MPa, and the thermal shock resistance is good.

[0044] Example 2 The present embodiment provides a method for preparing a carbon-ceramic composite brake disc by 3D printing. The raw materials of the carbon-ceramic composite brake disc include, by weight: 49 parts of modified chopped carbon fiber, 2 parts of boron carbide, 37 parts of photocurable resin, 4 parts of 75# microcrystalline wax, 5 parts of liquid paraffin, 3 parts of aluminum oxide, 3 parts of aluminum nitride, 3 parts of carbon black, 3 parts of octadecanoic acid, 2 parts of modified dispersant, 2 parts of fatty alcohol polyoxyethylene ether (emulsifier), 2 parts of ethanolamine, 2 parts of sucrose fatty acid ester, 3 parts of nitrile rubber powder, and 10 parts of styrene (organic solvent).

[0045] The particle size of the carbon black is 50 nm, the particle size of the aluminum oxide is 600 nm, and the particle size of the aluminum nitride is 10 μm.

[0046] The preparation method of the modified chopped carbon fiber comprises the following steps: heat-treating the chopped carbon fiber in an argon atmosphere at 1500° C. for 2.2 hours to remove metal ions and impurities on the surface of the chopped carbon fiber; then putting the chopped carbon fiber into acetone, ultrasonically cleaning it until there is no glue on the surface, placing it in an oven after cleaning, and drying it until the acetone is completely volatilized; then immersing the treated chopped carbon fiber into a modified treatment liquid, soaking it at 32° C. for 16 hours, washing it with distilled water, and then drying it to obtain the modified chopped carbon fiber.

[0047] The modified treatment liquid is an ethanol solution of tetraisopropyl di(dioctylphosphite) titanate; in the modified treatment liquid, the concentration of tetraisopropyl di(dioctylphosphite) titanate is 3.1wt%, and the concentration of the ethanol solution is 88%.

[0048] The diameter of the chopped carbon fibers was 10 μm and the length was 12 mm.

[0049] The preparation method of the modified dispersant comprises the following steps: mixing aluminum oxide, octadecanoic acid, sodium hyposulfite, N-(hydroxymethyl)acrylamide, diethylenetriamine, lauryl acrylate and deionized water in a mass ratio of 25:20:3:3:3:1:45, and then standing for 2 hours to obtain a mixture; placing the mixture in a vacuum homogenizer, performing vacuum homogenization for 0.7 hours at a vacuum degree of 0.02 MPa and a rotation speed of 3600 rpm, and placing the mixture in a 98° C. temperature environment after the vacuum homogenization, and drying for 100 minutes to obtain a slurry-state modified dispersant; The method for preparing a carbon-ceramic composite brake disc by 3D printing is specifically as follows: 1. Premix According to weight, short carbon fiber, boron carbide, adhesive, 75# microcrystalline wax, liquid paraffin, alumina, aluminum nitride, carbon black, octadecanoic acid, modified dispersant, emulsifier, ethanolamine, sucrose fatty acid ester, nitrile rubber powder, and organic solvent are put into a mixer, the stirring speed is controlled to 1000 rpm, and after stirring and mixing for 35 minutes, a premix is ​​obtained.

[0050] 2. Secret refining The premix prepared in the premixing step is introduced into the mixing chamber of the internal mixer, the temperature of the internal mixer is set to 230°C, the mixing speed is set to 13r / min, the internal mixer is turned on for heating and the main shaft is turned forward, and internal mixing is carried out; the state of the material in the internal mixer is observed at any time during the internal mixing process, and after 60 minutes of internal mixing, the material is viscous and has moderate hardness and softness, and the internal mixing is ended; the cooling is turned on, and the material in the internal mixer is cooled to 50°C, and then the material is discharged to obtain the internal mixed material.

[0051] 3. Granulation The mixed material obtained in the mixing step is placed in the feeding area of ​​the granulator, and the feeding temperature is set to 40°C and the feeding speed is set to 6r / min; the heating is turned on to pre-heat the screw zone and the discharging zone of the granulator, and the temperature of the screw zone is set to 200°C and the speed of the screw zone is set to 6r / min, the temperature of the discharging zone is set to 190°C and the speed of the discharging zone is set to 2.5r / min; after the temperatures of the screw zone and the discharging zone reach the set values, the screw of the feeding zone, the screw of the discharging zone and the screw zone are turned on in sequence to carry out granulation, and the discharging situation is observed during the granulation process, and the speed is fine-tuned according to the discharging situation to obtain granules with uniform particles and no adhesion.

[0052] 4. 3D printing Put the granules obtained in the granulation step into the hopper of the 3D printer, turn on automatic loading, use a nozzle with a diameter of 0.6mm, set the printing layer height to 0.2mm, the starting layer height to 0.25mm, the printing temperature to 230℃, the platform temperature to 130℃, and the printing speed to 50mm / s; and adjust the distance between the platform and the nozzle to 0.13mm; after importing the three-dimensional image of the brake disc into the slicing program, import the slicing program into the 3D printer for 3D printing, cool it after printing, and obtain the brake disc green body.

[0053] 5. Debinding The brake disc green body was placed in a vacuum environment of 0.05 MPa, and under the protection of a nitrogen atmosphere, the temperature was raised to 900°C, and the temperature was kept for 130 minutes for debinding. After the debinding was completed, the green body was cooled to room temperature to obtain a porous green body.

[0054] 6. Sintering The porous green body obtained in the debinding step is placed in a vacuum environment of 20Pa, silicon powder is added to the middle crucible where the porous green body is located, and then nitrogen is introduced as a protective gas, and the temperature is increased to 1900°C at a heating rate of 8°C / min, and the green body is sintered for 100 minutes; and during the sintering process, a suction device is used to suck the molten silicon powder into the porous green body; after the sintering is completed, the temperature is naturally cooled to room temperature to obtain a brake disc preform.

[0055] The added weight of silicon powder is 4% of the weight of the porous green body.

[0056] 7. Remove heavy assembly The powder and dust deposits in the grooves and pores of the sintered brake disc preform are cleaned up, and the preform is assembled according to the requirements of the drawing to obtain a carbon-ceramic composite brake disc to be inspected.

[0057] 8. Nondestructive testing An ultrasonic flaw detector is used to conduct finished product qualification test on the carbon-ceramic composite brake disc to be inspected. The test results are judged by the waveforms of longitudinal wave, transverse wave, surface wave and plate wave. If the test is qualified, the carbon-ceramic composite brake disc is produced.

[0058] After testing, the volume density is 2.90g / cm³, the bending strength is 420MPa, the friction coefficient is 0.41, and the wear rate is 0.32×10 -7 cm³ / (N·m), and can withstand high temperatures of 1920°C.

[0059] Furthermore, the carbon-ceramic composite brake disc of this embodiment is placed in a calcining furnace, and in an air atmosphere environment, the temperature is increased to 1200°C at a heating rate of 20°C / min, and after being kept warm for 10 hours, it is cooled to room temperature at a cooling rate of 10°C / min; after repeating this process 20 times, the bending strength of the carbon-ceramic composite brake disc can still reach 403MPa, and the thermal shock resistance is good.

[0060] Example 3 The present embodiment provides a method for preparing a carbon-ceramic composite brake disc by 3D printing. The raw materials of the carbon-ceramic composite brake disc include, by weight: 50 parts of modified chopped carbon fiber, 3 parts of boron carbide, 40 parts of photocurable resin, 2 parts of 75# microcrystalline wax, 3 parts of liquid paraffin, 2 parts of aluminum oxide, 2 parts of aluminum nitride, 4 parts of carbon black, 2 parts of octadecanoic acid, 3 parts of modified dispersant, 1 part of emulsifier, 2 parts of ethanolamine, 3 parts of sucrose fatty acid ester, 6 parts of nitrile rubber powder, and 8 parts of ethanol (organic solvent).

[0061] The particle size of the carbon black is 50 nm, the particle size of the aluminum oxide is 600 nm, and the particle size of the aluminum nitride is 10 μm.

[0062] The preparation method of the modified chopped carbon fiber comprises the following steps: heat-treating the chopped carbon fiber in an argon atmosphere at 1800° C. for 2.5 hours to remove metal ions and impurities on the surface of the chopped carbon fiber; then putting the chopped carbon fiber into acetone, ultrasonically cleaning it until there is no glue on the surface, placing it in an oven after cleaning, and drying it until the acetone is completely volatilized; then immersing the treated chopped carbon fiber into a modified treatment liquid, soaking it at 36° C. for 25 hours, washing it with distilled water, and then drying it to obtain the modified chopped carbon fiber.

[0063] The modified treatment liquid is an ethanol solution of tetraisopropyl di(dioctylphosphite) titanate; in the modified treatment liquid, the concentration of tetraisopropyl di(dioctylphosphite) titanate is 3.3wt%, and the concentration of the ethanol solution is 90%.

[0064] The diameter of the chopped carbon fibers was 10 μm and the length was 12 mm.

[0065] The emulsifier is composed of fatty alcohol polyoxyethylene ether and fatty acid methyl ester polyoxyethylene ether; the weight ratio of fatty alcohol polyoxyethylene ether to fatty acid methyl ester polyoxyethylene ether is 3:1.

[0066] The preparation method of the modified dispersant comprises the following steps: mixing aluminum oxide, octadecanoic acid, sodium hyposulfite, N-(hydroxymethyl)acrylamide, diethylenetriamine, lauryl acrylate and deionized water in a mass ratio of 17:19:3:3:2:1:55, and then standing for 3 hours to obtain a mixture; placing the mixture in a vacuum homogenizer, performing vacuum homogenization for 1 hour at a vacuum degree of 0.059 MPa and a rotation speed of 4000 rpm, and placing the mixture in a 100° C. temperature environment after the vacuum homogenization, and drying for 50 minutes to obtain a slurry-state modified dispersant.

[0067] The method for preparing a carbon-ceramic composite brake disc by 3D printing is specifically as follows: 1. Premix According to weight, short carbon fiber, boron carbide, adhesive, 75# microcrystalline wax, liquid paraffin, alumina, aluminum nitride, carbon black, octadecanoic acid, modified dispersant, emulsifier, ethanolamine, sucrose fatty acid ester, nitrile rubber powder, and organic solvent are put into a mixer, the stirring speed is controlled to 1300 rpm, and after stirring and mixing for 45 minutes, a premix is ​​obtained.

[0068] 2. Secret refining The premix prepared in the premixing step is introduced into the mixing chamber of the internal mixer, the temperature of the internal mixer is set to 250°C, the mixing speed is set to 15r / min, the internal mixer is turned on for heating and the main shaft is turned forward, and internal mixing is carried out; the state of the material in the internal mixer is observed at any time during the internal mixing process, and after 100 minutes of internal mixing, the material is viscous and has moderate hardness and softness, and the internal mixing is ended; the cooling is turned on, and the material in the internal mixer is cooled to 50°C, and then the material is discharged to obtain the internal mixed material.

[0069] 3. Granulation The mixed material obtained in the mixing step is placed in the feeding area of ​​the granulator, and the feeding temperature is set to 55°C and the feeding speed is set to 8r / min; the heating is turned on to pre-heat the screw zone and the discharging zone of the granulator, and the temperature of the screw zone is set to 240°C and the speed of the screw zone is set to 8r / min, the temperature of the discharging zone is set to 215°C and the speed of the discharging zone is set to 3.5r / min; after the temperatures of the screw zone and the discharging zone reach the set values, the screw of the feeding zone, the screw of the discharging zone and the screw zone are turned on in sequence to carry out granulation, and the discharging situation is observed during the granulation process, and the speed is fine-tuned according to the discharging situation to obtain granules with uniform particles and no adhesion.

[0070] 4. 3D printing Put the granules obtained in the granulation step into the hopper of the 3D printer, turn on automatic loading, use a nozzle with a diameter of 0.8mm, set the printing layer height to 0.35mm, the starting layer height to 0.35mm, the printing temperature to 250℃, the platform temperature to 140℃, and the printing speed to 55mm / s; and adjust the distance between the platform and the nozzle to 0.15mm; after importing the three-dimensional image of the brake disc into the slicing program, import the slicing program into the 3D printer for 3D printing, cool it after printing, and obtain the brake disc green body.

[0071] 5. Debinding The brake disc green body was placed in a vacuum environment of 0.06 MPa, and under the protection of a nitrogen atmosphere, the temperature was raised to 1100°C, and the temperature was kept for 300 minutes for debinding. After the debinding was completed, the green body was cooled to room temperature to obtain a porous green body.

[0072] 6. Sintering The porous green body obtained in the debinding step is placed in a vacuum environment of 30Pa, silicon powder is added to the middle crucible where the porous green body is located, and then nitrogen is introduced as a protective gas, and the temperature is increased to 2100°C at a heating rate of 9°C / min, and the green body is sintered for 120 minutes; and during the sintering process, a suction device is used to suck the molten silicon powder into the porous green body; after the sintering is completed, the temperature is naturally cooled to room temperature to obtain a brake disc preform.

[0073] The added weight of silicon powder is 5% of the weight of the porous green body.

[0074] 7. Remove heavy assembly The powder and dust deposits in the grooves and pores of the sintered brake disc preform are cleaned up, and the preform is assembled according to the requirements of the drawing to obtain a carbon-ceramic composite brake disc to be inspected.

[0075] 8. Nondestructive testing An ultrasonic flaw detector is used to conduct finished product qualification test on the carbon-ceramic composite brake disc to be inspected. The test results are judged by the waveforms of longitudinal wave, transverse wave, surface wave and plate wave. If the test is qualified, the carbon-ceramic composite brake disc is produced.

[0076] After testing, the volume density is 2.8g / cm³, the bending strength is 374MPa, the friction coefficient is 0.36, and the wear rate is 0.41×10 -7 cm³ / (N·m), and can withstand high temperatures of 1770°C.

[0077] Furthermore, the carbon-ceramic composite brake disc of this embodiment is placed in a calcining furnace, and in an air atmosphere environment, the temperature is increased to 1200°C at a heating rate of 20°C / min, and after being kept warm for 10 hours, it is cooled to room temperature at a cooling rate of 10°C / min; after repeating this process 20 times, the bending strength of the carbon-ceramic composite brake disc can still reach 360MPa, and the thermal shock resistance is good.

[0078] Comparative Example 1 Comparative Example 1 adopts the technical solution of Example 1, except that: 1) the preparation of modified chopped carbon fiber is omitted, and untreated raw chopped carbon fiber is used instead of modified chopped carbon fiber. 2) Sodium tripolyphosphate is used instead of modified dispersant, and the weight portion of sodium tripolyphosphate is adjusted to 2 parts.

[0079] In the process of 3D printing with the raw materials of comparative example 1, the extrusion performance of the raw materials was poor, and the printing molding had delamination and warping. The volume density of the brake disc finally obtained was 2.7g / cm³, the bending strength was 284MPa, the friction coefficient was 0.49, and the wear rate was 0.53×10 -7 cm³ / (N·m), heat-resistant temperature is 1535℃.

[0080] Furthermore, the carbon-ceramic composite brake disc of this comparative example was placed in a calcination furnace, and in an air atmosphere environment, the temperature was raised to 1200°C at a heating rate of 20°C / min, and after being kept warm for 10 hours, it was cooled to room temperature at a cooling rate of 10°C / min; after repeating this process 20 times, the flexural strength of the carbon-ceramic composite brake disc was 207MPa.

[0081] It can be seen from Comparative Example 1 that after using untreated chopped carbon fiber and replacing the modified dispersant with sodium tripolyphosphate, the mixing uniformity of the raw materials is reduced, the basic performance during the printing process is reduced, the extrusion printing output is uneven, and the printing molding effect is reduced; the wear resistance, mechanical properties and thermal shock resistance of the brake disc finally obtained are significantly reduced.

[0082] It can be seen from Examples 1-3 that the method for preparing a carbon-ceramic composite brake disc by 3D printing of the present invention is aimed at 3D printing characteristics. By adopting a specific amount of raw materials for combination, and using a coordinated titanate coupling agent solution to modify the heat-treated chopped carbon fibers in a targeted manner, modified chopped carbon fibers are prepared, and the effect of impurities in the chopped carbon fibers on the performance of the brake disc is improved while the bonding performance between the raw materials is improved; at the same time, a modified dispersant is pre-prepared using alumina, octadecanoic acid, sodium hyposulfite, N-(hydroxymethyl) acrylamide, diethylenetriamine, and lauryl acrylate, and the modified dispersant is combined with the raw materials to further improve the compatibility of the raw materials with 3D printing in a targeted manner. The raw materials are mixed, mixed and granulated to improve the uniformity of the raw materials and improve the extrusion of the raw materials during 3D printing. The performance is improved, the printing output is uniform, the uniformity of the prepared brake disc green body is improved, the clogging of the printer nozzle is further avoided, and the production efficiency is improved; then 3D printing is performed to prepare the brake disc green body, and the brake disc green body is subjected to processes such as debinding and sintering to obtain a carbon-ceramic composite brake disc, which can effectively reduce the waste of raw materials and improve the performance stability of the brake disc. At the same time, it can further overcome the problems of poor raw material extrusion performance, uneven printing output, and easy clogging of the 3D printer nozzle during the printing process when using existing carbon-ceramic materials to prepare brake discs and their ancillary parts by 3D printing, effectively improve the curing molding effect and production efficiency, improve the mechanical properties and wear resistance of the finally prepared carbon-ceramic brake disc, and thus improve the braking performance of the carbon-ceramic composite brake disc.

[0083] Unless otherwise specified, all percentages used in the present invention are by mass.

[0084] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon-ceramic composite brake disc by 3D printing, characterized in that: The following raw materials are used for preparation, in parts by weight: 45-70 parts of modified chopped carbon fiber, 1-5 parts of boron carbide, 30-40 parts of photocurable resin, 2-8 parts of 75# microcrystalline wax, 3-8 parts of liquid paraffin, 2-5 parts of aluminum oxide, 2-5 parts of aluminum nitride, 2-6 parts of carbon black, 2-6 parts of octadecanoic acid, 1-5 parts of modified dispersant, 1-3 parts of emulsifier, 1-3 parts of ethanolamine, 1-4 parts of sucrose fatty acid ester, 2-6 parts of nitrile rubber powder, and 8-20 parts of organic solvent; The raw materials are premixed, pounded and granulated, and then 3D printed to obtain a brake disc green body, and then debinding and sintering are performed to obtain a carbon-ceramic composite brake disc.

2. The method for preparing a carbon-ceramic composite brake disc by 3D printing according to claim 1, characterized in that: The preparation method of the modified chopped carbon fiber is as follows: the chopped carbon fiber is subjected to heat treatment in an argon atmosphere at 1200-1800° C., and then ultrasonically cleaned in acetone and dried; then, the chopped carbon fiber is immersed in a modification treatment liquid, immersed at 28-36° C. for 10-25 hours, washed with water, and dried to obtain the modified chopped carbon fiber; The modified treatment liquid is an ethanol solution of tetraisopropyl di(dioctylphosphite) titanate.

3. The method for preparing a carbon-ceramic composite brake disc by 3D printing according to claim 1, characterized in that: The preparation method of the modified dispersant comprises the following steps: uniformly mixing aluminum oxide, octadecanoic acid, sodium hyposulfite, N-(hydroxymethyl)acrylamide, diethylenetriamine, lauryl acrylate and deionized water and then standing the mixture to obtain a mixture; vacuum homogenizing the mixture and drying the mixture to obtain the modified dispersant.

4. The method for preparing a carbon-ceramic composite brake disc by 3D printing according to claim 1, characterized in that: The emulsifier is at least one of the following: fatty alcohol polyoxyethylene ether, fatty acid methyl ester polyoxyethylene ether, and sodium carboxymethyl cellulose; The organic solvent is at least one of the following: ethanol, tetrahydrofuran, styrene, perchloroethylene, and ethylene glycol ether.

5. The method for preparing a carbon-ceramic composite brake disc by 3D printing according to claim 2, characterized in that: In the preparation of the modified chopped carbon fiber, the heat treatment time at 1200-1800° C. is 2-2.5 hours; In the modified treatment solution, the concentration of tetraisopropyl di(dioctylphosphite) titanate is 3-3.3wt%, and the concentration of the ethanol solution is 85-90%; The diameter of the chopped carbon fiber is 6-20 μm and the length is 2-20 mm.

6. The method for preparing a carbon-ceramic composite brake disc by 3D printing according to claim 3, characterized in that: In the preparation of the modified dispersant, the mass ratio of aluminum oxide, octadecanoic acid, sodium hyposulfite, N-(hydroxymethyl)acrylamide, diethylenetriamine, lauryl acrylate and deionized water is 12-35:15-30:3-5:3-8:2-5:1-2:25-55.

7. The method for preparing a carbon-ceramic composite brake disc by 3D printing according to claim 1, characterized in that: The method for preparing the premix comprises: uniformly mixing short carbon fiber, boron carbide, adhesive, 75# microcrystalline wax, liquid paraffin, alumina, aluminum nitride, carbon black, octadecanoic acid, modified dispersant, emulsifier, ethanolamine, sucrose fatty acid ester, nitrile rubber powder, and organic solvent according to weight to obtain a premix; The banburying method comprises: performing banburying treatment on the premix to obtain a banburying product; The granulation method comprises: granulating the mixed material to obtain granules; The 3D printing method comprises: using a 3D printing nozzle with a diameter of 0.4-0.8 mm, setting a printing layer height of 0.15-0.35 mm, a starting layer height of 0.15-0.35 mm, a printing temperature of 210-250° C., a platform temperature of 100-140° C., and a printing speed of 35-55 mm / s; and adjusting the distance between the platform and the nozzle to 0.13-0.15 mm; after 3D printing, cooling, and obtaining a brake disc green body; The debinding method comprises: performing debinding treatment on a brake disc green body to obtain a porous green body; The sintering method comprises: adding silicon powder into the middle crucible where the porous green body is located under vacuum conditions, and then sintering at 1530-2100° C. under nitrogen protection to obtain a brake disc preform; The brake disc preform is subjected to weight removal, assembly and non-destructive testing to obtain a carbon-ceramic composite brake disc.

8. The method for preparing a carbon-ceramic composite brake disc by 3D printing according to claim 7, characterized in that: In the banburying, the banburying temperature is 210-250° C., the banburying speed is 10-15 r / min, and the banburying time is 50-100 min; During the debinding, the vacuum degree is controlled to be 0.04-0.06 MPa, the debinding temperature is 700-1200° C., and the heat preservation debinding time is 80-360 min.

9. The method for preparing a carbon-ceramic composite brake disc by 3D printing according to claim 7, characterized in that: In the granulation, the banburying material obtained in the banburying step is placed in the feeding zone of the granulator, the feeding temperature is set to 35-55°C, and the feeding speed is 5-8r / min; the heating is turned on, and the screw zone and the discharging zone of the granulator are preheated, and the temperature of the screw zone is set to 180-240°C, the speed of the screw zone is 5-8r / min, the temperature of the discharging zone is set to 170-215°C, and the speed of the discharging zone is 1.5-3.5r / min; granulation is carried out to obtain granules.

10. The method for preparing a carbon-ceramic composite brake disc by 3D printing according to claim 7, characterized in that: During the sintering, the heating rate to 1530-2100°C is 7-9°C / min; 1530-2100℃ holding time is 65-130min; The added weight of silicon powder is 3-10% of the weight of the porous green body.